TOLERANSI BERAGAMA DI LINGKUNGAN PESANTREN: ANALISIS TERHADAP MADZHAB AHLUS SUNNAH WAL-JAMA’AH - Mahatma, Masmuni (FASTABIQ: JURNAL STUDI ISLAM, 2022)
This study aims to analyze the attitude of religious tolerance of the salaf pesantren community affiliated with Nahdlatul Ulama in relation to the religious understanding that develops in pesantren, in this case it is the understanding of Ahlus Sunnah Wal Jama'ah. The research method used is a qualitative approach with literature studies. The results of this study concluded that pesantren communities are people who understand the concepts of religious tolerance. Since a long time ago, pesantren have always maintained an inclusive religious understanding and accepted various differences in madzhab, thought, and religion. In relation to the diversity of Indonesia in terms of agam, the Pesantren community has first applied the attitude of tasamuh and respect for fellow human beings based on the teachings of Ahlus Sunnah Wal-Jama'ah which connects to the teachings of the Prophet Muhammad SAW. The research is expected to be an epiphany for Muslims, especially to explore the religion of pesantren which clearly teaches kindness and tolerance towards different people. In the future, this diverse Indonesian society can live in harmony in differences.Keywords: Mazhab Ahlus Sunnah Wal-Jama'ah, Pesantren, Tolerance